PEMULIHAN PONDOK DAUD: LANDASAN TEOLOGIS DAN PEMBARUAN PUJIAN PENYEMBAHAN PENTAKOSTA MASA KINI - Twin Yoshua R. Destyanto; Dony Lubianto; Jono; Minerva Gabriela Tuanakotta (The Way: Jurnal Teologi dan Kependidikan, 2022)
Pentecostal praise and worship always develop time by time. The pattern changes can be understood as a continuous process of church restoration from time to time towards the apostolic church. The restoration of Tabernacle of David (RTOD) is proposed to be a reference for Pentecostals to formulate the theological foundation in renewing the pattern of praise and worship in the present era. This paper aims to (i) explain the theological basis of the Pentecostal pattern of praise and worship in today's era, (ii) explain the theological meaning of RTOD prophecy and its relationship to praise and worship, and (iii) explain the application of RTOD in renewal of the Pentecostal praise and worship in the present era. This paper uses a qualitative method by applying a systematic literature study and phenomenological approaches to understand the theological basis of praise and worship pattern, the meaning of RTOD in general and related to praise and worship, components in RTOD, and its application in praise worship. The results of the study show that the RTOD can be used as a theological foundation and renewal of Pentecostal praise and worship in the present era.So, it can be concluded that the theological basis and definition RTOD can be used as a reference for applying it in the praise and worship of today's Pentecostals.